\(\left(5n+12\right)⋮\left(n-3\right)\)
\(\Rightarrow5\left(n-3\right)+27⋮\left(n-3\right)\)
\(\Rightarrow\left(n-3\right)\inƯ\left(27\right)=\left\{1;-1;3;-3;9;-9;27;-27\right\}\)
Do \(n\in N\)
\(\Rightarrow n\in\left\{0;2;4;6;12;30\right\}\)
Ta có: 5n+12 ⋮ n-3
⇔ 5(n-3)+27 ⋮ n-3
⇔ 27⋮n-3 hay n-3∈Ư(27)
mà n là số tự nhiên
⇒ n-3≥-3
hay n-3={-3;-1;1;3;9;27}
⇔ n= {0;2;4;6;12;30}
Ta có: \(5n+12⋮n-3\)
\(\Leftrightarrow5n-15+27⋮n-3\)
\(\Leftrightarrow n-3\in\left\{1;-1;3;-3;9;-9;27;-27\right\}\)
hay \(n\in\left\{4;2;6;0;12;-6;30;-24\right\}\)